DESIGNING INCLUSIVE LANGUAGE ASSESSMENTS FOR LEARNERS WITH SPECIAL EDUCATIONAL NEEDS - Aktamova Zarnigor Yahyo qizi; Khonsaidova Maktuba Makhamadalievna (TADQIQOTLAR, 2026)
This article explores principles and practical strategies for designing accessible and equitable language assessments. It highlights differentiated assessment formats, the use of assistive technologies, flexible timing, multimodal input/output options, and simplified language without reducing academic rigor. The discussion emphasizes that inclusive assessment is not about lowering standards but about providing equitable pathways for all learners to demonstrate their abilities. Ultimately, inclusive assessment design contributes to more accurate evaluation, improved learner motivation, and greater educational equity.